Anti-diabetic potential of Psidium guajava leaf in streptozotocin induced diabetic rats - Toluwani Tella; Bubuya Masola; Samson Mukaratirwa (Elsevier, 2022)
Background: Psidium guajava is a medicinal plant with antidiabetic properties and can be found growing in tropical and sub-tropical countries around the world. Purpose: The aim of the present study was to investigate the anti-diabetic potential of Psidium guajava leaf in streptozotocin-induced diabetic rats, with particular focus on key enzymes of glycogen metabolism in skeletal muscle. Study design: The study design involved preparation of an aqueous Psidium guajava leaf extract; investigation of its effect on muscle glycogen synthase and phosphorylase activities and possible protective effect on pancreas in streptozotocin induced diabetic male Sprague-Dawley rats and phytochemical study of the extract to identify further compounds with anti-diabetic potential. Method: Diabetes was induced in male Sprague-Dawley rats with a single intraperitoneal injection of 40 mg/kg streptozotocin. Normal and diabetic animals were treated with 400 mg/kg body weight of Psidium guajava leaves aqueous extract for a period of 14 days. Results: The treatment of diabetic animals with the Psidium guajava extract ameliorated damage to the pancreatic islets and enhanced lowering of blood glucose following a glucose load. Diabetes significantly decreased (P < 0.05) glycogen synthase activity by 31% compared to normal animals this being associated with a decrease in enzyme expression. Psidium guajava treatment returned the enzyme activity to near normal levels. In diabetic animals, glycogen phosphorylase activity was elevated but not significantly (P > 0.5) and treatment of both diabetic and normal animals with the extract reduced activity of the enzyme. The Psidium guajava extract also reduced glycogen phosphorylase expression in diabetic animals. Skeletal muscle glycogen content reduced by diabetes was increased as a result of treatment of diabetic animals with the Psidium guajava extract. Phytochemical analysis of the aqueous extract of Psidium guajava using Gas Chromatography-Mass Spectroscopy indicated the presence of triterpenes and phenolic compounds and we also report what we believe are three new compounds. Conclusion: The results from this study suggest that the antidiabetic effects of Psidium guajava may be due to modulation of glycogen metabolism mediated by phenolic compounds and triterpenes present in the extract.